2021
DOI: 10.14814/phy2.14858
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and the potential for regulating glucose metabolism in cardiomyocytes during insulin resistance and T2DM

Abstract: In order for the heart to maintain its continuous mechanical work and provide the systolic movement to uphold coronary blood flow, substantial synthesis of adenosine triphosphate (ATP) is required. Under normal conditions cardiac tissue utilizes roughly 70% fatty acids (FA), and 30% glucose for the production of ATP; however, during impaired metabolic conditions like insulin resistance and diabetes glucose metabolism is dysregulated and FA account for 99% of energy production. One of the major consequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Under normal conditions, fatty acids and glucose are the primary energy sources for the heart to maintain continuous systolic movement to support cardiac pumping. However, during aberrant metabolic conditions such as diabetes and insulin resistance, glucose utilization by cardiomyocytes decreases, while the utilization of fatty acids and ketone bodies increases ( 45 ). Cardiomyocytes need to adapt to these energy transitions to maintain myocardial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, fatty acids and glucose are the primary energy sources for the heart to maintain continuous systolic movement to support cardiac pumping. However, during aberrant metabolic conditions such as diabetes and insulin resistance, glucose utilization by cardiomyocytes decreases, while the utilization of fatty acids and ketone bodies increases ( 45 ). Cardiomyocytes need to adapt to these energy transitions to maintain myocardial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, thyroid hormones promote the entry of glucose and fatty acids into cells, increasing the supply of substrates for cellular respiration, including the TCA cycle [50]. In addition, these molecules boost the activity of enzymes involved in the TCA cycle and the electron transport chain, leading to increased ATP production [51]. In hypothyroidism, with reduced levels of thyroid hormones, the overall cellular metabolism tends to slow down.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings supporting the shift in phenylalanine metabolism towards transcinnamate production instead of tyrosine in PD, we assume that the lower levels of tyrosine in P lead to the production of lower levels of thyroxine, resulting in developing hypothyroidism. Since we had excluded any participant with a history of thyroid dysfunction disorder or on thyroid hormone replacement therapy and given that thyroxine regulates glucose metabolism (Mendez and Ortiz, 2021), we assessed the levels of glucose-6-phosphate between P and C. Our results showed that P have significantly lower levels of this metabolite, confirming our hypothesis that the shift in phenylalanine metabolism that led to a decrease in the levels of tyrosine has an impact on thyroxine level and its physiological TABLE 5 Represents the significant differences (p-value%) in the levels of the tackled metabolites between the different recruited groups: C vs. P, P vs. HC, and C vs. HC. The yellow shaded cells shows insignificant difference, while the orange cells represents metabolites that were significantly higher in P than in C; however, the rest of the metabolites were significantly higher in C than in P. functions as a consequence.…”
Section: Tyrosine Metabolismmentioning
confidence: 99%